Quality Control Analysis Into Decrease the Level Defects on Coffee Product - Heri Wibowo; . Sulastri; Emy Khikmawati (International Conference on Engineering and Technology Development (ICETD), 2013)
Many local companies were that engaged in the manufacturing of coffee beans into semi-finished carelessly ready for export. To maintain the product to fit customer demand, it is very necessary quality control. The problems are the following: (1) The destruction of coffee still within the limits of control or not. (2) Any type of damage that occurs in coffee product were produced. (3) The factors that cause damage to the coffee product. (4) Application of statistical tools in controlling product quality coffee and pressing the occurrence of damage to the product. This study aims to determine how the implementation of quality control using statistical tools useful in efforts to control the level of damage to the product in the company. P control chart analysis results indicate that the process is in a state of uncontrolled or still experiencing irregularities. Based on Pareto diagram, priority repairs that need to be done is for the dominant type of damage that the black seed (25.68%), broken seeds (19.23%), brown seeds (17.60%) and more than a hollow seeds (15.99%). the causal diagram analysis can be seen from the factors that cause damage to human factors/workers, machine production, work methods, materials/raw materials and the work environment, so the company can take precautions and repair the damage.